Redefining Islamic Tradition: Legal Interpretation as a Medium for Innovation in the Making of Modern Morocco - Terem, Etty (Islamic law and society, 2013)
In 1910, as the possibility that Morocco would fall to French control threatened to overwhelm the Muslim community, al-Mahdī al-Wazzānī, a distinguished Moroccan Islamic scholar, penned the conclusion of his massive compilation of Mālikī fatwās and named it the New Mi‘yār. This essay explores the nature and meaning of the New Mi‘yār. I argue that al-Wazzānī did not merely assemble a collection of fatwās, but deliberately formulated a text that was firmly rooted in the specific challenges and changes generated by Moroccan modernity and was designed to redefine Mālikī legal tradition to make it relevant to his time. For al-Wazzānī, redefining Mālikī tradition and thought as an effective regulator of contemporary social relations and Islamic morality was necessary to reinforce the authority of Mālikī scholarship and to ensure the moral survival of the Muslim community in the context of the dramatic transformations that characterized Moroccan modernity.